Studying GATA3, FOXA1, and ELF5 transcription factors in the evaluation of prognosis in luminal breast cancer patients - S. V. Vtorushin; D. V. Vasilchenko; M. V. Zavyalova; N. V. Krakhmal’; S. V. Patalyak (Бюллетень сибирской медицины, 2021)
Background. The identification of predictive molecular markers of luminal breast cancer will help to assess the risk of developing distant metastases and determine a personalized approach to predicting the outcome of the disease during hormone therapy.The aim of the study was to investigate the relationship between the transcription factors GATA3, FOXA1, and ELF5 in the tumor and the occurrence of distant metastases in patients with luminal subtype of breast cancer during adjuvant hormone therapy.Materials and methods. The study included 101 patients with breast cancer (aged from 30 years to 81 years, average age (54.8 ± 10.3) years), with stages T1–4N1–3M0 of the disease. The follow-up period was at least 5 years. The inclusion criteria for the study were luminal molecular genetic subtype of the tumor and lack of preoperative treatment. The exclusion criterion was stage IV disease. The study of transcription factors was carried out by the immunohistochemical method using polyclonal antibodies to GATA3, FOXA1, and ELF5, manufactured by Flarebio (Austria).Results. Low expression of FOXA1 and ELF5 in the tumor was associated with the development of distant metastases (p = 0.000015 and p = 0.000002, respectively). In addition, it was found that high incidence of hematogenous metastases was associated with heterogeneous expression of FOXA1 (χ2 = 6.42; p = 0.01) and ELF5 (χ2 = 14.46; p = 0.0001) in the tumor. No similar differences were found in the study of GATA3 expression.Conclusion. The level of expression of transcription factors FOXA1 and ELF5 and their distribution in the primary tumor can be considered as potential molecular markers in assessing the risk of hematogenous metastasis in patients with luminal breast cancer.